2009
DOI: 10.1042/cs20080162
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase 4D gene polymorphism is associated with ischaemic and haemorrhagic stroke

Abstract: It has been reported that the variants of the PDE4D (phosphodiesterase 4D) gene are associated with stroke, especially with the combination of cardio-embolic and carotid stroke in the Icelandic population, but it is still very controversial as to whether PDE4D is a susceptible gene for stroke in other populations. In the present study, we tested whether the PDE4D gene variation also confers stroke risk in a Chinese population. Our hypothesis was tested in a case-control study of a Chinese population comprising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 20 publications
2
23
0
Order By: Relevance
“…Subsequently, Bevan et al [83] performed a study in a non-Icelandic European population and found a possible association with CE stroke, but the lack of an association found with carotid IMT and plaque would suggest a mechanism other than accelerated atherosclerosis. However, the role of PDE4D is inconclusive, with some investigators [84,85] replicating the association and some not [86] . Despite extensive genotyping of the PDE4D locus, the disease-causing genetic variant has not been identified thus far.…”
Section: Matrix Metalloproteinases (Mmps)mentioning
confidence: 99%
“…Subsequently, Bevan et al [83] performed a study in a non-Icelandic European population and found a possible association with CE stroke, but the lack of an association found with carotid IMT and plaque would suggest a mechanism other than accelerated atherosclerosis. However, the role of PDE4D is inconclusive, with some investigators [84,85] replicating the association and some not [86] . Despite extensive genotyping of the PDE4D locus, the disease-causing genetic variant has not been identified thus far.…”
Section: Matrix Metalloproteinases (Mmps)mentioning
confidence: 99%
“…Also, it seems possible that the effect of PDE4D on stroke varies between populations depending on different genetic backgrounds and environmental influences [34]. The study by Xue et al demonstrated that allele C of rs966221 in PDE4D gene conferred a 1.5-fold risk for atherothrombotic strokes in a Chinese population [35], supporting that PDE4D acts through atherosclerosis. 4.7 ALOX5AP and the leukotriene pathway ALOX5AP is another gene that has been discovered through genome-wide linkage analysis.…”
Section: Phosphodiesterase 4dmentioning
confidence: 97%
“…In this meta-analysis, we included 7 more studies (i.e. Lövkvist et al [16] , Matsushita et al [29] , Lin et al [31] , Banerjee et al [32] , Munshi et al [33] , Xue et al [34] , and Sun et al [35] ) published after the study by Bevan et al [17] . Among the 6 SNPs analyzed, our metaanalysis of 7 homogenous studies showed a significant association between SNP56 and ischemic stroke (p = 0.022).…”
Section: Discussionmentioning
confidence: 99%
“…We performed a meta-analysis in Asian groups (i.e. Matsushita et al [29] , Saleheen et al [30] , Lin et al [31] , Xue et al [34] , and Sun et al [35] ) and found no evidence of a genetic association of SNP87 with ischemic stroke. After removing Staton et al [13] from the initial analysis, the heterogeneity of SNP89 significantly decreased.…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation